2017
DOI: 10.1098/rstb.2016.0031
|View full text |Cite
|
Sign up to set email alerts
|

Invasions and extinctions through the looking glass of evolutionary ecology

Abstract: One contribution of 18 to a theme issue 'Human influences on evolution, and the ecological and societal consequences'. Invasive and endangered species reflect opposite ends of a spectrum of ecological success, yet they experience many similar eco-evolutionary challenges including demographic bottlenecks, hybridization and novel environments. Despite these similarities, important differences exist. Demographic bottlenecks are more transient in invasive species, which (i) maintains ecologically relevant genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 165 publications
(196 reference statements)
1
106
0
1
Order By: Relevance
“…There are reasons to expect that invasive species may respond more rapidly than native species to climate change [11]. Additionally, we found that interspecific differences in habitat and life history had strong effects on phenological shifts under climate change-much stronger than enemy release.…”
Section: Model Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…There are reasons to expect that invasive species may respond more rapidly than native species to climate change [11]. Additionally, we found that interspecific differences in habitat and life history had strong effects on phenological shifts under climate change-much stronger than enemy release.…”
Section: Model Results and Discussionmentioning
confidence: 64%
“…These factors can constrain evolutionary responses to selection (e.g. [83][84][85]) and may favour invasive species over native species with sparse populations [11]. Thus, incorporating delayed evolutionary responses would potentially slow the evolution of flowering time and reduce reproductive fitness in native populations more than introduced populations.…”
Section: Model Results and Discussionmentioning
confidence: 99%
“…The introduction of species to new regions is one such activity that exerts strong selective pressure [52,53], and the introduction of pathogens to novel host communities is no exception [26]. WNS has caused severe declines in North American bats (more than 90% mortality in several species) and has thereby exerted intense selective pressure on bat populations to evolve traits to persist with this pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the greatest increases in genetic variation will attend contexts where population sizes increase most dramatically, such as for introduced species experiencing 'enemy release' [35,68] and for native species benefiting from 'disappearing diseases' [38]. Increases are also expected when diverse source populations are brought together in new locations [34,69,70] and in the case of exposure to mutagens (e.g. pollution [71,72]).…”
Section: Human Influences On Evolution (Figure 3)mentioning
confidence: 95%